Research advances of femtosecond laser-induced nanogratings for transparent materials - Lu, Yue; Li, Yunfei; Xie, Xiaofan; Tang, Ziqi; Li, Lifang; Li, Jiawei; Ding, Yu (Frontiers in Chemistry, 2022)
Femtosecond laser-induced nanogratings generation inside transparent materials has been the focus of research in the field of femtosecond laser precision processing. Due to the advantages of optical birefringence phenomenon, periodicity, thermal stability, controllability of delay value and optical axis direction, and re-writability, nanogratings are widely used in research fields such as optical storage and optical devices. This mini-review explores the existing mechanism of femtosecond laser-induced formation of nanogratings and the progress of inducing nanogratings in different types of glass and sapphire crystals. It also describes the prospects of nanogratings for a wide range of applications in optical components and optical devices.